Evaluation of a mathematics program for preprimary children in rural Bangladesh - Opel, Aftab; Zaman, Syeda Sazia; Khanom, Ferdousi; Aboud, Frances E. (© 2012 Elsevier Ltd, 2016)
This article was published in the International Journal of Educational Development [© 2011 Elsevier Ltd. ] and the definite version is available at : http://doi.org/10.1016/j.ijedudev.2011.01.013. The Journal's website is at: http://www.sciencedirect.com/science/article/pii/S0738059311000149